Philosophical Approaches in the Utilisation of Conflict Management : Understanding and Managing Conflict in Social and Organisational Environments - Indira Oktavianti; Landreas Utama Lie; Agung Winarno; Heri Pratikto (International Journal of Economics and Management Sciences, 2024)
This study aims to analyse the use of conflict management in the view of philosophy as an additional insight in the context of social science and management, where with the right conflict management including by paying attention to philosophical aspects, it will foster new opportunities in achieving goals for organisational development. Through a literature review approach, the results show that the use of conflict management through philosophical views can open up new opportunities for organisational management that are considered to be able to solve conflicts effectively. By understanding conflict and managing it well, organisations can develop dynamically and productively, especially in creating better innovations to achieve common goals.